1992
DOI: 10.1177/0011128792038002010
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: The Death Sentence and Inmate Attitudes

Abstract: Public opinion surveys show that the American public favors capital punishment. This article examines the attitudes of 307 inmates about capital punishment. The respondents, especially the most violent offenders, favored capital punishment for some crimes when applied to others, but not to their own criminal activity. Moreover, they did not see capital punishment as a deterrent and implied that it reinforces their violent perspectives. Incarcerated offenders apparently feel as strongly as other citizens about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
2
9
2
Order By: Relevance
“…One implication arising from this finding is that neither the threat of prison nor long prison sentences are a deterrence of crime. This thought finds congruence with earlier research suggesting that criminally violent offenders are rarely afraid of incarceration or capital punishment (Stevens 1992a(Stevens , 1992b. American prisons seem to inadequately protect society and long prison terms under authoritative regimes seem to undermine the social values that were intended to curb crime.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…One implication arising from this finding is that neither the threat of prison nor long prison sentences are a deterrence of crime. This thought finds congruence with earlier research suggesting that criminally violent offenders are rarely afraid of incarceration or capital punishment (Stevens 1992a(Stevens , 1992b. American prisons seem to inadequately protect society and long prison terms under authoritative regimes seem to undermine the social values that were intended to curb crime.…”
Section: Resultssupporting
confidence: 87%
“…Additionally, male inmates most likely to anticipate a crime-free future were those who had spent the least time in prison and vice versa. This thought is also consistent with the argument that perceived severity of sentence including capital punishment is little deterrent to criminality (Bursik, Grasmick and Chamlin 1990;Stevens 1992aStevens , 1992b.…”
Section: Length Of Time-served Contributed To Expectations Of Crimesupporting
confidence: 83%
“…This finding suggests extremely high concordance between the two groups of inmates on the ranking of offender types. Given the work of Vaughn (1990a, 1990b) and others (Akerstrom, 1986;Stevens, 1992) on sex-offending and homicidal inmates, this finding must be viewed as relatively strong evidence for the importation of general values about crimes and offenders from the street into prisons.…”
Section: Values and Prisoners: Inmate Views On Earning Respect And Extending Respectmentioning
confidence: 87%
“…Attitudes toward the death penalty provide an instructive case in point. Stevens (1992) explored support for the death penalty among maximum and minimum security inmates incarcerated in Illinois, North Carolina, and South Carolina. Noting that the majority of the public supports capital punishment, Stevens (1992, p. 275) reported that many prison inmates also supported the increased use of the death penalty to rid society of unwanted and dangerous individuals.…”
Section: Inmate Culture and Prisoner Valuesmentioning
confidence: 99%
“…Thus, researchers check their survey/interview data with prison files (Scully 1990). But, this process violates the confidentiality and candor of the respondents (Peterson, Harriet and Polich 1984;Stevens 1992b); therefore, the participants in this study were asked potentially dangerous questions without revealing their identity.…”
Section: Methodsmentioning
confidence: 99%